Polyvinylidene Difluoride–Polyethyleneoxide Blends for Electrospun Separators in Li-Ion Batteries. Issue 1 (1st January 2017) - La Monaca, A.; De Giorgio, F.; Focarete, M. L.; Fabiani, D.; Zaccaria, M.; Arbizzani, C.
Abstract : Polyvinylidenedifluoride (PVdF) and polyethyleneoxide (PEO) are blended and electrospun in order to obtain membranes suitable as Li-ion battery separators. The separators are characterized, and their properties investigated and compared with those of PVdF and commercial separators. The PVdF-PEO based separators ensure increased conductivities, greater electrolyte uptake and higher porosities than commercial polyolefines, all factors that improve cell performance. They are also safer than PVdF separators thanks to lower shutdown temperature, even if their mechanical properties are not yet comparable with those of the latter.